Caregivers' engagement during in‐hospital care of sABI's patients: Evaluation of informal co‐production from the health providers' perspective. (2nd June 2020) - Farnese, Maria Luisa; Girardi, Giovanna; Fida, Roberta; Bivona, Umberto; Bartolo, Michelangelo; De Tanti, Antonio; Intiso, Domenico; Scarponi, Federico; Antonucci, Gabriella
Abstract: One of the challenges of providing healthcare services is to enhance its value (for patients, staff and the service) by integrating the informal caregivers into the care process, both concretely managing their patient's health conditions and treatment (co‐executing) and participating in the whole healthcare process (co‐planning). This study aims at exploring the co‐production contribution to the healthcare process, analysing whether and how it is related to higher caregivers' satisfaction with service care and reduced staff burnout, in the eyes of the staff. It also investigated two possible factors supporting caregivers in their role of co‐producers, namely relationship among staff and informal caregivers related to knowledge sharing (i.e. an ability determinant supporting co‐production) and related to role social conflict (i.e. a willingness determinant reducing co‐production). Results of a structural equation model on a sample of 119 healthcare providers employed by neurorehabilitation centers in Italy with severe acquired brain injury confirmed that knowledge sharing positively related with caregivers' co‐executing and co‐planning. Also, social role conflict was negatively related with co‐executing but positively with co‐planning. Furthermore, co‐planning resulted in being unrelated to both outcomes, whereas co‐executing was associated with caregivers' satisfaction, as measured by staff perceptions. Overall, our data provided initial empirical evidence supporting the ability of the determinant's contribution in allowing informal caregivers to assume an active role in both co‐production domains. Furthermore, as expected, the role of conflict willingness determinant was found to be a hindering factor for co‐executing but, conversely, a trigger for co‐planning. This result should be considered more carefully in future studies.